Introduction to the Special Issue: Measurement Based Care in Youth Depression and Suicidality. - Slater, Holli; Guzick, Andrew G. (Child Psychiatry & Human Development, 2025)
Herein we introduce the Collection "Measurement Based Care in Youth Depression and Suicidality." Measurement-based care (MBC), or the systematic use of measurement tools to inform treatment decisions, has been identified as a key component of providing evidence-based psychiatric care. However, the implementation of MBC at the clinic or health system level is not trivial; barriers to successful implementation are widespread but can be overcome. This Collection presents five manuscripts that cover a range of topics related to the implementation of MBC. The first two articles provide guidance to clinicians and researchers in careful selection of validated measurement tools for depression and suicidality. Next, our authors describe an effort to assess the fidelity of MBC use across the Texas Youth Depression and Suicide Research Network registry study, a statewide longitudinal cohort of depressed and suicidal youth. The following article outlines the benefits, barriers, and implementations strategies to implementing MBC at the health system level. Our final article details the implementation of MBC into a health system and provides data on screening outcomes and related clinical associations.